PROPOSED BUSINESS STRATEGY FOR PERSADA MEDICAL CLINIC TO INCREASE COMPETITIVENESS AND PROFITABILITY - Rachmah Sari, Fitha
Persada Medical Clinic, as a newcomer in the health and beauty industry, faces challenges in entering the market. However, they recognize the potential profitability of the industry. They are aware that competition from existing industry players may pose barriers to their smooth operations. Financial reports indicate a decrease in net sales and average daily transactions since March. Additionally, the number of registered BPJS members falls short of the clinic's target. Patient visits for primary healthcare and beauty treatments average at five and two per day, respectively. The clinic acknowledges the absence of a specific strategy to achieve their goals. To increase competitiveness and profitability, Persada Medical Clinic needs to develop a business strategy to establish a competitive advantage. This research combines qualitative and quantitative methods. Qualitative techniques involve observation, company visits, and interviews, while quantitative methods utilize numerical techniques, statistical analysis, and rating-based questionnaires. The data extracted through descriptive analysis and SWOTAnalysis Hierarchy Process (AHP-SWOT). The strategy formulation involved an analysis of the external environment using PESTEL, Porter's Five Forces, and Competitor Analysis. Meanwhile, internal analysis using Value Chain Analysis, Four Criteria of Sustainable Advantages, and the STP model. The findings indicate that the health and beauty industry in Indonesia is moderately to highly attractive and competitive. The competition is intense, and customers seek the best value products. Persada Medical Clinic appears to adopt a cost leadership approach, aiming to compete on cost and streamlining processes for increased profitability. The clinic's competitive advantage is classified as competitive parity to temporary competitive, with average to above-average returns. The TOWS Matrix suggests 16 alternative strategies to be implemented within 24 months. However, the absence of a monitoring and evaluation system in this research makes it challenging to assess the effectiveness of each implemented strategy.